PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR BERBASIS KETERAMPILAN BERPIKIR SEBAGAI ALTERNATIF IMPLEMENTASI KBK - Weldi Bahari (PGSD Universitas Negeri Medan, 2018)
Deeply exploring the contents of Law Number 20 of 2003 concerning the Indonesian education system, it can be drawn two important aspects that must be achieved by elementary education institutions, namely: providing a basis for life in society, and can continue education. Mathematics education in Indonesia needs to be reformed, especially in the Teacher learning strategies used by teachers. This is because until now many students complain and experience difficulties in learning mathematics. Mathematics is a ghost that is frightening to most elementary school students. This is because one of the characteristics of mathematics learning is abstract.Keywords: Mathematics, Learning, Mind Based Learning.